Gadara, Jordanien. 749 AD. Ein Erdbebenhorizont am höchsten Punkt des Siedlungsareals. Auszug aus den Arbeiten der Jahre 2015, 2018 und 2019 - Bührig, Claudia; Hamel, Hanna; Möller, Heike; Watkins, Luna (e-Forschungsberichte des DAI, 2021)
The ongoing archaeological research at the ancient site of Gadara, Jordan, conducted jointly with the Department of Antiquities of Jordan has set its focus in the last years to the hilltop, the area of the upper village of Umm Qays, called Hara Foqa. The report presents an overview on the activities done in the last years with focus on a building-complex, probably destroyed by the earthquake in 749 CE. Its embedding into a broader context gives a first insight into the settlement history and development at the highest point of the ancient town. It shows the potential of an area that was left in Umayyad times and resettled more than thousand years later, when families started building their houses there again.